Bacteriostatic and Bactericidal Effect of Tigecycline on Leptospira spp. - Fabrizio Bertelloni; Giovanni Cilia; Filippo Fratini (MDPI AG, 2020)
Tigecycline is a relatively new antimicrobial, belonging to glycylcyclines with antimicrobial activity against a large spectrum of bacteria. Very few data are available on its effect on Leptospira spp., which consist in a bacteriostatic mechanism. The aim of this investigation was to evaluate the bacteriostatic and bactericidal effect of tigecycline on reference Leptospira strains belonging to 16 serovars. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined through the microdilutions method, and tetracycline was used as the control. Results showed that tigecycline had higher MIC and MBC values than tetracycline. Obtained MIC values were between 4 and 32 µg/mL, while MBC values between 16 and >128 µg/mL. Patoc (MIC: 4 µg/mL; MBC: 16 µg/mL) resulted in the most susceptible serovar, while the most resistant were Bataviae (MIC: 32 µg/mL; MBC: 64 µg/mL), Bratislava (MIC: 8 µg/mL; MBC 128 µg/mL), and Tarassovi (MIC: 8 µg/mL; MBC: >128 µg/mL). This is the first investigation focused on the effect of tigecycline against Leptospira spp. reference strains. Since tigecycline is used as a treatment for bacteremia and urinary tract disease, and these symptoms could be linked to Leptospira infection, the possibility of using this antibiotic as a treatment for leptospirosis should be evaluated. Further studies are needed to explore the possibility to use tigecycline for in vivo application against Leptospira.